Türkiye’de sigara bırakma polikliniklerinin erişilebilirliği: İstanbul’da sigara içen bir popülasyon arasında tanımlayıcı bir çalışma - SAVE, DİLŞAD (My University, 2022)
Objective: In 2011, Turkey started the nationwide \"Smoking Cessation Treatment Support Program\" via Smoking Cessation Clinics (SCC). This study examined the accessibility of these clinics using Levesque’s framework of access to healthcare services. From the (potential) users’ perspectives, it was aimed to find the challenges they face in accessing these clinics, and it proposed solutions for better implementation. Methods: This study was conducted among 304 smokers who visited four Family Health Centers in a geographically defined area in Istanbul, Turkey, in 2018. Result: In this study, it was found that 74% of smokers wished to quit smoking. Within them, 21% didn’t know of SCCs, and half of them didn’t know what services were provided there. Among those who knew of SCCs, 30% used them to quit smoking. The majority (75.7%) of the SCC users found the medications expensive; 41% didn’t use them, and 64% didn’t re-visit the clinics for follow-ups. Eventually, 4.3% of smokers quit smoking through SCCs. Utilization of these clinics were significantly higher among women (35%) than men (18.6%) (p=0.024). T; and there was no other differences in terms of age, marital status, income, and education level. Conclusion: Smoking cessation programs in Turkey and other countries can be implemented more efficiently if the sufficient number of clinics are opened and are accessible at the local level; more health professionals are trained to practice; the clinics are made more visible; smoking cessation medications are made available constantly; and closer monitoring of service users is ensured. Keywords: Smoking Cessation, Access To Health Care, Health Plan Implementations, Turkey
Keywords: Tıp; Dahili Tıp Bilimleri; Halk Sağlığı; Epidemiyoloji; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Public Health; Epidemiology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; SAĞLIK BAKIM BİLİMLERİ VE HİZMETLERİ; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; HEALTH CARE SCIENCES & SERVICES; MEDICINE, GENERAL & INTERNAL; Tıbbi Terminoloji; Tıbbi Sekreterlik ve Transkripsiyon; Sağlık Bilgi Yönetimi; Sağlık Meslekleri (çeşitli); Genel Sağlık Meslekleri; Gözden Geçirme ve Sınav Hazırlığı; Patofizyoloji; Liderlik ve Yönetim; Temel Bilgi ve Beceriler; Toplum Sağlığı ve Evde Bakım; Bakım Planlaması; Değerlendirme ve Teşhis; Dahiliye; Sağlık Politikaları; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; Medical Terminology; Medical Assisting and Transcription; Health Information Management; Health Professions (miscellaneous); General Health Professions; Review and Exam Preparation; Pathophysiology; Leadership and Management; Fundamentals and Skills; Community and Home Care; Care Planning; Assessment and Diagnosis; Internal Medicine; Health Policy; Family Practice; Medicine (miscellaneous); General Medicine